Urinary Tract Enterococcal Infections And Their Antimicrobial Resistance - DR. ANJANA TELKAR,; DR. BARAGUNDI MAHESH C,; DR. RAGHAVENDRA V.P.,; DR. VISWANATH G, (International Journal of Pharma and Bio Sciences, 2012)
Context : Enterococci have emerged as second most common cause of nosocomial infections since the last decade. The most frequent infections caused by enterococci are urinary tract infections (UTIs). Enterococci also have become resistant to wide range of antibiotics. Aim : The present study was done to determine the prevalence of different enterococcal species in urinary tract infections and their antimicrobial resistance with special reference to vancomycin and high level aminoglycoside resistance. Material and methods : Study was conducted on 80 enterococcal urine isolates. The isolates were identified by standard microbiological techniques and antibiotic sensitivity testing was done by Kirby – Bauer disc diffusion method according to CLSI guidelines. Results : Maximum enterococci were isolated from male patients in the age group of 0-20 years. Most of the enterococci (71.25%) were non hemolytic and multidrug resistant. E.faecalis (65%) was the predominant species isolated. Linezolid and nitrofurantoin showed good antienterococcal activity. Vancomycin resistance was seen in 11 (13.75%) isolates and high level aminoglycoside resistance was seen in 44 (55%) of isolates. E.faecium isolates were more drug resistant than E.faecalis isolates. Conclusion : Steps should be taken to regularly screen enterococcal isolates for vancomycin and high level aminoglycoside resistance and treat enterococcal infections effectively to limit spread of multidrug resistant enterococcal infections.